Diagnosis Of Brucellosis In Buffalo Serum By Polymerase Chain Reaction (Applied Biological Research, 2014)
Brucellosis, a chronic infectious disease, is worldwide in distribution. Though it has been eradicated  in many developed countries, it still remains an uncontrolled serious public health problem in most  of the developing countries (Refai, 2002). Brucellosis is caused by the members of genus Brucella.  Bovine brucellosis is mostly caused by B. abortus, and less frequently by B. melitensis (OIE, 2009).  Oral route is the common portal of entry of this agent (Crawford et al., 1990). The main clinical  signs of brucellosis are abortion, retained placenta, still births and orchitis (Enright et al., 1984). Laboratory diagnosis of brucellosis can be made by various primary and secondary binding  immuno-assays. However, unequivocal diagnosis requires bacteriological demonstration of the  agent. As isolation of this agent is laborious and poses potential health hazard to the laboratory  workers, an alternative to it is polymerase chain reaction (PCR). PCR has been applied for the  diagnosis of Brucella species (Rijpens et al., 1996). Previous studies have documented the use of  different clinical specimen viz., peripheral blood of human (Queipo-Ortuno et al., 1999), buffaloes  (Guarino et al., 2000), dog (Keid et al., 2009), goat milk (Leal-Klevezas et al., 1995), human serum  (Zerva et al., 2001), camel (Alshaikh et al., 2007) and sheep (Singh et al., 2010) for the diagnosis  of Brucella species by PCR. The present study describes the application of PCR for diagnosis of  brucellosis in serum samples from buffalo.
Keywords: Diagnosis; Buffalo; Reaction